Measurement of the Characteristics of TIDs Using Small and Regional Networks of GPS Receivers during the Campaign of 17–30 July of 2008 - Cesar E. Valladares; Matthew A. Hei (International Journal of Geophysics)
This scientific report presents the results of a dedicated experiment that was conducted within the framework of the Low-latitude ionospheric Sensor Network (LISN) observatory to measure the characteristics of medium-scale (hundreds of km) Traveling Ionospheric Disturbances (TIDs) as they transit through the low-latitude ionosphere. A small array of 3 GPS receivers separated by 4-5 km placed in a triangular configuration was installed near Huancayo in Peru possessing several characteristics of a radio-interferometer. During the campaign days, 17–30 July 2008, TIDs were observed daily. On July 20, 2008 between 22 and 24 UT several TIDs moved across the small array of GPS receivers with a velocity near 130 m/s, were directed northward and had wavelengths close to 450 km. Other GPS receivers that were operating hundreds of km away from Huancayo show also similar TEC traces and provide a phase velocity equal to 150 m/s. This value was measured using the GPS at Piura, Cuzco and Huancayo. Based on this positive result, we conclude that small and/or regional arrays of GPS receivers can be used at low latitudes to study the role that gravity waves may have on seeding plasma bubbles.